Microstructure evolution and mechanical properties of Al–Cu alloys inoculated by FeBSi metallic glass. (15th February 2015) - Bai, Zhihao; Qiu, Feng; Chi, Jiaxuan; Zhang, Tao; Jiang, Qichuan
Highlights: The FeBSi metallic glass can act as inoculant to refine α-Al dendritic grains for Al–Cu alloys. A significant refining effect of α-Al grain can be achieved by addition of FeBSi metallic glass. Within an inoculation time of 30 min, the inoculated Al–Cu alloys remain a fine grained structure. The strength and ductility of the inoculated alloys are simultaneously improved. Abstract: A significant refining effect of α-Al grains from 200 μm to 42 μm can be achieved by addition of 0.1 wt.% FeBSi metallic glass, which is mainly attributed to the crystallization of Fe2 B phase being able to act as the heterogeneous nucleation sites of α-Al grains during solidification. Within an inoculation time of 30 min, the inoculated Al–Cu alloys remain a fine grained structure. Moreover, the strength and ductility of the inoculated alloys are simultaneously improved. The enhanced properties of Al–Cu alloy inoculated by metallic glass are mainly due to the refined α-Al grains, the small θ ′ precipitates distributed homogeneously in grain interior and the formation of the nano-sized AlCuFeMn phase. This study provides a high-efficiency and cost-effective processing technique of refinement in this alloy, and at the same time, broadens the industry application of metallic glass.